METHODS OF DEVELOPING STUDENTS' CRITICAL THINKING SKILLS (INTERNATIONAL JOURNAL OF RECENTLY SCIENTIFIC RESEARCHER'S THEORY, 2024)
This article recommends ways students can develop critical thinking skills. It also aims to help students express their personal opinions freely and prove their opinions with evidence.